TRUSTED AUTHENTICATION AND SECURITY OF MEDICAL DATA IN CLOUD COMPUTING - K. RAMKUMAR; DR.G.GUNASEKARAN (International Journal of Pharma and Bio Sciences, 2015)
Cloud computing provides shared, on-demand and scalable services over internet with user’s data being processed in remote machines and required services provided. The main barrier in using this new technology in different field is the users fear on data security, availability and integrity of their own data in remote servers. In this paper, an efficient cloud storage system for storing medical records of patients between hospitals located in different countries with data security and integrity has been proposed. Multifactor authentication for user login to cloud, homomorphic encryption for storing the data with integrity checking has been used effectively in the proposed system. Experimental study has been done to demonstrate the effectiveness of the proposed approach.